PENDAMPINGAN DAN SOSIALISASI PERATURAN PERPAJAKAN TERBARU BAGI KOPERASI PEGAWAI REPUBLIK INDONESIA LEMBAGA PENGEMBANGAN DAN PEMBERDAYAAN KEPALA SEKOLAH (KPRI LPPKS) - Salim, Meka Sabilla (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
This community service activity is conducted for the management and staff of the Koperasi Pegawai Republik Indonesia (KPRI) Lembaga Pengembangan dan Pemberdayaan Kepala Sekolah (LPPKS). The activities begin with a socialization session on the management and bookkeeping of cooperatives in accordance with Financial Accounting Standards (SAK). Then, a socialization session on the latest tax regulations was held, including the new TER policy for calculating Employee Income Tax and other changes in tax regulations. Following this, a seminar on taxation and financial governance for the management and administrators of the cooperative is held. The activities are then followed by assisting the management and staff of the cooperative in preparing financial statements and tax reports. The goal of these activities is to enhance the understanding of accounting and taxation among the management and staff of KPRI LPPKS.